Industrialized building system (IBS)-the effect of plywood thickness on the profiled steel sheeting dry board screw stiffness through push out test - Nor Azilla, Rozali (2014)
The issue of the influx of foreign workers has not subsided despite many measures taken by the Government to tackle the problem. The repercussion of the issue has become very apparent such that there are increased outflow of money to other countries, heightened social problems, the low quality, productivity and delay in works and not to mention, the spread of deadly diseases. Moreover, the availability of cheap foreign workers in Malaysia has made the construction players prefer the conventional systems. To solve these problems, IBS has been proposed in several studies as the solution to reduce the construction time and the dependency on foreign workers in construction industry. Industrialized Building System (IBS) technology has changed the past practices of the construction industry which in turns greatly improves the quality and safety of the building sector. Profiled Steel Sheeting Dry Board (PSSDB) system is classified as a one of the IBS. This research goal is to give a better understanding of the behavior of the PSSDB floor panel before it can be regarded as an innovative, competitive system that can increase the acceptance of IBS in the construction sector. The research objectives are, firstly, to determine the strength of the connection screws through the push out test and secondly, to compare the screw stiffness of the sample with different plywood thicknesses. Parametric studies were conducted by using different thicknesses of plywood. For the study of effect of plywood thickness, the Peva45 as Profiled Steel Sheeting is fixed at 0.8 mm, while the thickness of plywood varied at 12 mm, 18 mm and 20 mm. Laboratory experiments results show that there was a 42 % and 5% increase in stiffness of the samples when the plywood thickness is increased from 12 mm to 20 mm and from 12 mm to 18 mm, respectively. The thicker of the plywood, the stiffer the panel will be. This information can add new understanding of the PSSDB system which has the potential to be expanded to better meet the requirement of the IBS construction.